Adoption of internet of things along halal food- based SMEs supply chain in Malaysia / Hazwani Ahmad Tarmizi ... [et al.] - Ahmad Tarmizi, Hazwani; Kamarulzaman, Nitty Hirawaty; Abd Rahman, Azmawani; Atan, Rodziah (Academy of Contemporary Islamic Studies (ACIS), Universiti Teknologi MARA (UiTM), 2019)
In the food industry particularly, the supply chain involves multilevel players from suppliers to end consumers. In uplifting food supply chain safety value, the halal concept has been introduced to the food industry in addition to other existing safety certificates such as Good Agricultural Practice (GAP), Hazard Analysis and Critical Control Points (HACCP), and Good Manufacturing Practice (GMP). The halal supply chain ensures high quality production of halal food and is a new realm with immense market potential driving the global economy. The efficiency along the food supply chain integrated with the advent of technology has boosted the applicability of products traceability system. The use of Internet of Things (IoT) in the traceability system has facilitated supply chain players in managing their products information along the chain. As one of the significant halal industry players, SMEs are slow in adopting IoT. With IoT, halal food-based SMEs supply chain will no doubt provide a trusted platform but the number of halal scandals and issues in the market continues to increase. Therefore, the objective of this study was to investigate the adoption of IoT along halal food-based SMEs supply chain in Malaysia. Data were gathered among selected 30 halal food-based SMEs based on self-administered questionnaires. The results showed that most of the halal food-based SMEs displayed a low level of IoT adoption in managing their halal products production processes. Therefore, radical changes are necessary for implementing IoT among Malaysian halal food-based SMEs.